Pengaruh Return On Asset (ROA), Current Ratio (CR) , Dan Pertumbuhan Penjualan Terhadap Harga Saham Pada Perusahan Sub Sektor Property dan Real Estate Yang Terdaftar Di BEI Periode 2019-2021 - Kholida Atiyatul Maula; Dewangga Kreshnadjati (Peneliti.net, 2022)
This study aims to obtain empirical evidence and analyze the Effect of Return On Assets (ROA), Current Ratio (Cr), and Sales Growth on Stock Prices. The population in this study are property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The total sample used in this study was 22 companies based on the established criteria. The sampling technique uses purposive sampling, the type of data is secondary data. Data analysis was carried out with descriptive analysis test, classical assumption test, and hypothesis testing with multiple linear regression analysisThe results of this study indicate that return on assets (ROA) has no effect on stock prices, current ratio (CR) has no effect on stock prices, and sales growth has no effect on stock prices. And together return on assets (ROA), current ratio (CR) and sales growth affect stock prices